MEMBANGUN STRATEGI MEMENANGKAN PASAR PERSAINGAN PADA TOKO PAKAIAN DI KOTA TEGAL - sujarwo, makmur (Benefit: Jurnal Manajemen dan Bisnis, 2018)
Abstract : This research is aimed to find out how far the improvement of store operation excellence, the increase of store communication effectiveness (visual merchandising), area trading optimization, focused marketing activity and community involvement have been built in clothing stores in Tegal city so that the retailers can win market competition.This study used a sample of 100 clothing stores in the city of Tegal as respondents. Respondents answers to the closed questions about the variables studied in this study were then analyzed by using Multiple Regression Test while the answer to the open question was analyzed qualitatively.The results of this study indicate that increased communication effectiveness in the shop, focused marketing activities and community involvement significantly influence the strategy to win the clothing store retail market in the city of Tegal. For that it should be clothing store retailers can further improve these three variables to win more competitive market.Of the five variables above, the community involvement variable has the greatest effect for retailers to win the competition market with a score of 0.251. So a retailer to be more active in social activities by providing compensation to the poor and orphans.Â Keywords: Market winning strategy, excellence store operations, visual merchandising, area trading optimization, focused marketing activities and community involvement.Â